Rasayana : A Safe Guarder Towards Non-Communicable Disease Review Article - Sv, Suvitha; Yadav, Sarika; Yadav, Chhaju Ram (International Research Journal of Ayurveda & Yoga, 2021)
Non communicable diseases are one of the major challenging issues facing worldwide, especially in developing countries in the 21st century, not only in terms of human sufferings but also its badly affecting the socioeconomic development of the country. According to the WHO report, NCD’s are collectively responsible for the death of around 41 million people each year, equivalent to 71% of all deaths worldwide. Also, they report that if timely intervention is not done for the prevention and control of NCD’s, the death rate will increase to 55 million by 2030. Due to the unplanned rapid urbanization, globalisation of unhealthy lifestyles and population ageing, people are more prone to lifestyle disorders such as cardiovascular disease, respiratory disorders, cancers, diabetes etc. Being a part of the health-care delivery system, this is the time to re-analyse the health management system and look back at the philosophy of prevention and preservation as the first step to treatment. Ayurveda is the system which focuses mainly on preventive aspects and considered it as prime or foremost objective. Various diet and regimens are mentioned in Ayurveda to maintain good healthy life style such as Dinacharya, Ritucharya, Sadvritta, Pathya apathya, Aharavidhi, Aharakalpana, Dharaniya and adharaniya vega, Sodhana ,Achara Rasayana, Rasayana etc.Among that, Rasayana tantra is one among the Astanga of Ayurveda which highly stresses preservation of health and prevention of disease. Based on our today’s hurry burry lifestyle, it’s the basic need for everyone to follow and include this Rasayana therapy in our day-to-day schedule to maintain health and prevent various lifestyle disorders. Rasayana is an effective preventive technique towards non-communicable disease.